Pengaruh Intellectual Capital, Financial Risk, dan Enterprise Risk Management Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub-sektor Makanan & Minuman - Suminarti; Setyowati, Tupi; Maharani, Novita (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
This research investigates the impact of Intellectual Capital, Financial Risk, and Enterprise Risk Management on Firm Value in the food and beverage industry. The sample consists of 9 companies listed on the Indonesia Stock Exchange for the 2018-2022 period, with 45 data points collected using purposive sampling. Secondary data was sourced from financial information available on www.idx.co.id. Multiple linear regression analysis was applied. The study's findings reveal that only Financial Risk has a significant positive effect on Firm Value, while Intellectual Capital and Enterprise Risk Management do not show a significant impact. These results contradict previous research. Based on these findings, it is recommended that companies focus on optimizing financial risk management, particularly in leveraging debt for operations, while still considering the importance of Intellectual Capital and Enterprise Risk Management. These factors may provide long-term benefits for the company despite their current lack of a direct impact on Firm Value.